"Rules of Engagement" of Protein–Glycoconjugate Interactions: A Molecular View Achievable by using NMR Spectroscopy and Molecular Modeling. Issue 4 (7th June 2016) - Marchetti, Roberta; Perez, Serge; Arda, Ana; Imberty, Anne; Jimenez‐Barbero, Jesus; Silipo, Alba; Molinaro, Antonio
Abstract: Understanding the dynamics of protein–ligand interactions, which lie at the heart of host–pathogen recognition, represents a crucial step to clarify the molecular determinants implicated in binding events, as well as to optimize the design of new molecules with therapeutic aims. Over the last decade, advances in complementary biophysical and spectroscopic methods permitted us to deeply dissect the fine structural details of biologically relevant molecular recognition processes with high resolution. This Review focuses on the development and use of modern nuclear magnetic resonance (NMR) techniques to dissect binding events. These spectroscopic methods, complementing X‐ray crystallography and molecular modeling methodologies, will be taken into account as indispensable tools to provide a complete picture of protein–glycoconjugate binding mechanisms related to biomedicine applications against infectious diseases. Abstract : Rules of engagement : This review focuses on the development and use of modern nuclear magnetic resonance (NMR) techniques, complementing molecular modeling methodologies, able to provide a complete picture of protein–glycoconjugate binding mechanisms related to biomedicine applications against infectious diseases.